Production of Biochar by Pyrolysis of Food Waste Blends for Negative Carbon Dioxide Emission - Zsolt Dobó; Helga Kovács; Gábor Nagy (Energies)
A negative carbon emission scenario via pyrolysis of three different food waste blends was investigated. A tube reactor was utilized for pyrolysis runs at temperatures of 650 °C, 725 °C, and 900 °C, while the carbon inventory was prepared. The blend of rice and french fries resulted in the highest char yield, being 212 g/kg at 650 °C pyrolysis temperature. In this case, each kg of food waste can correspond to 536 g of captured or removed CO2 from the air. The blend of roast pork and breaded chicken showed significantly less carbon removal potential of 348 gCO2/kgsample measured at 650 °C pyrolysis temperature, compared to rice and French fries. A higher pyrolysis temperature resulted in lower char yields, but, on the other side, it resulted in a higher carbon content of char. Additionally, higher pyrolysis temperature resulted in lower carbon capture potential within the temperature range utilized in this study. The heating value of dry pyrolysis gas was between 12.0–16.6 MJ/Nm3 and 10.3–12.3 MJ/Nm3 during the heat-up and constant temperature period, respectively. Based on the results, negative CO2 emission can be reached via pyrolysis of food waste with the benefit of capturing carbon in solid form, and therefore, this method can be considered a promising and alternative method to treat food waste.